Supplementary material from "A radiocarbon bomb pulse model for estimating the age of North Atlantic cetaceans" ... - Garde, Eva; Ditlevsen, Susanne; Olsen, Jesper; Heide-Joergensen, Mads Peter (The Royal Society, 2024)
The tusk of the male narwhal is a prolonged canine tooth, reaching a size of up to three meters in length. The tusk erupts through the young narwhal’s upper left lip and, over time, develops into an elongated structure, composed of dentine growth layers with an outer coating of cementum. In this study, we utilized bomb radiocarbon ( 14 C) to estimate the ages of three narwhal tusks, which allowed us to validate the assumption that one growth layer is deposited annually in narwhal tusks. We used radiocarbon values from samples collected from the annual growth layers along the lengths of the erupted tusks and from the tip and base of embedded teeth, together with published radiocarbon data from three North Atlantic whale species, for the purpose of building a model of the incorporation of bomb radiocarbon in marine mammal tissues. The results obtained contributes significantly to our understanding of narwhal growth and longevity, enhancing our comprehension of isotope flow in the Arctic marine environment and ...